Radiopharmaceuticals for Persistent or Recurrent Uterine Cervix Cancer - Kunos, Charles A.; Capala, Jacek; Kohn, Elise C.; Ivy, Susan Percy (Frontiers in Oncology, 2019)
Uterine cervix cancers pose therapeutic challenges because of an overactive ribonucleotide reductase, which provides on-demand deoxyribonucleotides for DNA replication or for a DNA damage repair response. Ribonucleotide reductase overactivity bestows cancer cell resistance to the effects of radiotherapy and chemotherapy used to treat disease; but nevertheless, this same biologic overexpression provides opportune vulnerabilities relatively specific to uterine cervix cancers for new therapeutic strategies to take advantage. The discovery of human epidermal growth factor receptor 2 (ErbB2 or HER2) overexpression on metastatic uterine cervix cancer cells provides an opportunity for clinical trials of targeted radiopharmaceuticals in combination with DNA damage response modifying drugs. The National Cancer Institute's clinical trial infrastructure and its experimental therapeutics portfolio can now offer clinical trial evaluation of molecularly-targeted and tolerated radiopharmaceutical-drug combinations for women with persistent or recurrent metastatic uterine cervix cancer. This article discusses the current thinking of the National Cancer Institute in regard to attractive radiopharmaceutical strategies for this disease and others.